REGULATING NETWORK VOLTAGES OF UNBALANCED LV GRIDS USING A DISTRIBUTED REACTIVE POWER CONTROL SYSTEM (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
The demand for renewable energy rather than fossil fuels is on the increase. This paper suggests a novel control technique for voltage regulation in unbalanced LV distribution networks featuring substantial decentralized renewable energy generation shares. The proposed technique relies heavily on the reactive power of distributed renewable energy sources. Additionally, its distinguishing characteristic is the application of a distributed control architecture that gives priority to DRES responses to keep network voltages within safe parameters and to reduce network losses. In this model, decisions are made locally by each DRES using information from the sensitivity theory, local measurements, and measurements acquired by the other network DRESs. By running time-domain and time-series simulations, it was concluded that the proposed model outperforms decentralized solutions and exhibits near-optimal behavior compared to optimization-based methods but with less computation complexity and monitoring requirements.